2015
DOI: 10.1016/j.ymgmr.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Muscle imaging data in late-onset Pompe disease reveal a correlation between the pre-existing degree of lipomatous muscle alterations and the efficacy of long-term enzyme replacement therapy

Abstract: BackgroundLate-onset Pompe disease (LOPD) is a metabolic myopathy caused by mutations in GAA and characterized by proximal muscle weakness and respiratory insufficiency. There is evidence from clinical studies that enzyme replacement therapy (ERT) with human recombinant alpha-glucosidase improves motor performance and respiratory function in LOPD.ObjectiveWe analyzed quantitative muscle MRI data of lower limbs to evaluate the effects of long-term ERT on muscle parameters.MethodsThree symptomatic LOPD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Our pilot study confirms the usefulness of MRI to delineate affected muscles in PD [ 9 , 12 , 14 16 ]. The pattern of involvement was similar in patients with and without ERT [ 14 ] and disease severity and duration were correlated to quantitative MRI findings.…”
Section: Discussionsupporting
confidence: 80%
“…Our pilot study confirms the usefulness of MRI to delineate affected muscles in PD [ 9 , 12 , 14 16 ]. The pattern of involvement was similar in patients with and without ERT [ 14 ] and disease severity and duration were correlated to quantitative MRI findings.…”
Section: Discussionsupporting
confidence: 80%
“…However, in these patients, fatty infiltration and muscle size and shape changes can hamper accurate segmentation, thereby possibly decreasing the reproducibility. Nevertheless, the main difficulty here is distinguishing between muscles, which currently has to be performed manually by an experienced examiner, which is time‐consuming, requires a lot of experience, and is currently the only limiting factor of a fully automated processing pipeline. However, provided muscles of patients are segmented correctly and similarly across centers, the reproducibility should still be similar for patients, as shown for fat fraction in DMD patients …”
Section: Discussionmentioning
confidence: 99%
“…A literature review revealed inconsistency about whether T1- or T2-weighted images are preferred when assessing fatty muscle degeneration by conventional MR sequences. While the majority of authors prefer T1-weighted sequences [ 13 , 17 , 27 , 28 ], others have used T2-weighted images [ 19 , 25 ]. T2-weighted imaging risks overestimating fatty muscle degeneration because fat, edema, and high glycogen content appear hyperintense; thus, T1-weighted images would be preferable to monitor Pompe disease.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of fatty muscle degeneration by MRI using grayscale values based on signal intensity has been reported using T1-weighted images [ 17 ]. Another group recently introduced a quantification method based on signal intensity measurements of the paraspinal muscles in relation to a small encircled area of subcutaneous fat from the same level [ 18 ].…”
Section: Introductionmentioning
confidence: 99%